THE IMPACT OF THE COVID-19 PANDEMIC ON THE LABOR SECTOR IN INDONESIA: A MULTIVARIATE ANALYSIS OF VARIANCE APPROACH (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The COVID-19 pandemic has affected the development of the labor sector. The economic impact of restrictions and lockdowns during the pandemic has resulted in job declines, mass layoffs, and financial uncertainty for many workers. This study aims to conduct a comparative analysis of the development of the labor sector in Indonesia before and during the COVID-19 pandemic. The data analysis tool used in this study is Multivariate Analysis of Variance (MANOVA). One of the uses of this analysis is to perform comparison or difference tests. This analysis is carried out through the stages of multivariate normality tests, homogeneity tests, simultaneous comparison tests (multivariate) and comparison tests separately (univariate). The results of the study concluded that multivariately there were significant differences in labor development in Indonesia between before and during the COVID-19 pandemic.
Keywords: labor sector development; comparative analysis; manova; covid-19 pandemic